Utilitarianism’s response to virtue ethics (Diametros, 2007)
The subject of the article is the current debate between virtue ethics and the proponents of utilitarianism, who represent one of the most important ethical conceptions present in analytic philosophy. Among other things, advocates of virtue ethics blame utilitarianism and ethics based on the deontological model for the long absence of virtue in thinking about morality; they do not accept the strong consequentialist suppositions of utilitarianism and criticize the fundamental ambiguity of the category of happiness in this theory.A closer analysis of contemporary utilitarianism shows that the objections of advocates of virtue ethics have been overcome in some of the positions formulated on the ground of utilitarianism. Moreover, there have also appeared several attempts to reinterpret utilitarianism in the spirit of virtue ethics, for example, R. Crisp’s virtue utilitarianism, R. Adams’ motive utilitarianism, and P. Railton’s value utilitarianism. This seems to imply that the basic principles of utilitarianism and virtue ethics are not as divergent as has often been assumed.